(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The Qur’anic recitations, with their different names, are an abundant material for grammarians in general and Ibn Malik in particular in explaining the facilitation.Keywords: Ibn Malik, readings, Arabic grammar.